Lapatinib Ameliorates Experimental Arthritis in Rats - Ozgen, Metin; Koca, Suleyman Serdar; Karatas, Ahmet; Dagli, Adile Ferda; Erman, Fazilet; Gundogdu, Baris; Isik, Ahmet (Springer/Plenum Publishers, 2015)
Epidermal growth factor receptor (EGFR) and its ligands are commonly expressed by synovial cells. The aim of the present study was to detect the potential effect of lapatinib an inhibitor of EGFR tyrosine kinases on collagen-induced arthritis. Thirty Wistar albino female rats were randomized into three groups. Arthritis was induced by intradermal injection of chicken type II collagen with incomplete Freund's adjuvant. Serum TNF-alpha, IL-17, and malondialdehyde (MDA) levels were analyzed. Tissue superoxide dismutase (SOD), catalase and glutathione peroxidase (GPx) activities, and nuclear factor erythroid 2-related factor-2 (Nrf2) and heme oxgenase-1 (HO-1) expressions were determined. TNF-alpha, IL-17 and MDA levels, and Nrf2 and HO-1 expressions were lower in lapatinib-treated (30 mg/kg/day) group compared to sham group, while SOD, catalase, and GPx activities were higher (p < 0.05). Moreover, lapatinib ameliorated perisynovial inflammation and cartilage-bone destruction (p < 0.001). In conclusion, EGFR may have prominent pathogenic role and lapatinib may be an effective therapeutic option for arthritis.
Keywords: collagen-induced arthritis; epidermal growth factor; lapatinib